2005
DOI: 10.1161/circulationaha.104.505248
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Prosthesis–Patient Size on Functional Recovery After Aortic Valve Replacement

Abstract: Background-Prosthesis-patient size mismatch results when an implanted prosthetic aortic valve is of insufficient size for a patient's body surface area. The relation between prosthesis-patient size and functional capacity and adverse postoperative outcome is inconsistent. Our objectives were to examine the impact of valve replacement, continuous prosthesis-patient size, and other factors on functional recovery after aortic valve replacement (AVR) with the Duke Activity Status Index (DASI

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 42 publications
4
46
0
2
Order By: Relevance
“…[4][5][6][7][8] In the present study, preoperative left ventricular function was relatively normal in all groups, especially in the PPM group. Moreover, the patients in the present study were relatively young.…”
Section: Discussionsupporting
confidence: 47%
See 3 more Smart Citations
“…[4][5][6][7][8] In the present study, preoperative left ventricular function was relatively normal in all groups, especially in the PPM group. Moreover, the patients in the present study were relatively young.…”
Section: Discussionsupporting
confidence: 47%
“…Many studies have also shown that small functional prostheses with an EOAI < 0.85 cm 2 /m 2 , do not adversely affect outcomes in elderly AVR patients or in young patients with high cardiac output requirements. [4][5][6][7][8] In the present study, the risk of aortic root enlargement could not be evaluated due to the small number of subjects enrolled. However, aortic root enlargement reportedly increases the operative risk.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Koch and his colleague stated that factors other than PPM infl uence functional quality of life early after AVR. 15 Howell and his colleagues, using multivariate analysis, showed that emergent surgery, LVEF (<30%), female sex, concomitant coronary artery bypass grafting, age (>80 years), and prolonged cross-clamping time were predictive of in-hospital mortality following AVR, whereas PPM was not. 16 Echocardiographic analysis also showed that PPM did not affect LVM regression rate after AVR in the midterm.…”
Section: Discussionmentioning
confidence: 99%